2018
DOI: 10.3390/nu10010103
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Acid Load and Potassium Intake Associate with Blood Pressure and Hypertension Prevalence in a Representative Sample of the German Adult Population

Abstract: Diets rich in fruits and vegetables, like the Dietary Approaches to Stop Hypertension (DASH)-diet, are usually characterized by high potassium intake and reduced dietary acid load, and have been shown to reduce blood pressure (BP). However, the relevance of potential renal acid load (PRAL) for BP has not been compared with the relevance to BP of urinary biomarker (K-urine)- and dietary food frequency questionnaire (K-FFQ)-based estimates of potassium intake in a general adult population sample. For 6788 partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 52 publications
1
28
0
Order By: Relevance
“…Several other studies also reported similar results of higher prevalence of HTN or higher SBP and DBP values in highest vs lowest PRAL or NEAP groupings . Only one study reported inverse association between HTN prevalence among NEAP quartiles and several other studies found no difference . In the data analysis of Rotterdam study by Engberink et al, SBP in the highest tertile of PRAL was significantly higher than the lowest.…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…Several other studies also reported similar results of higher prevalence of HTN or higher SBP and DBP values in highest vs lowest PRAL or NEAP groupings . Only one study reported inverse association between HTN prevalence among NEAP quartiles and several other studies found no difference . In the data analysis of Rotterdam study by Engberink et al, SBP in the highest tertile of PRAL was significantly higher than the lowest.…”
Section: Resultsmentioning
confidence: 69%
“…Table presents the summary of systematically reviewed studies evaluated the association between dietary acid load (eg PRAL or NEAP), blood pressure and hypertension prevalence. Totally, 20 studies reported the association between HTN, blood pressure and PRAL or NEAP among the systematically reviewed literature . In the study by Akter et al evaluating the association between dietary acid load and prevalence of HTN in the Furukawa Nutrition and Health Study the odds of HTN in subjects in the highest tertile of PRAL and NEAP was 31% and 40% more than individuals in lowest tertile (PRAL; OR: 1.31; CI: 1.01‐1.70; NEAP OR: 1.40; CI: 1.08‐1.82) among 2028 working Japanese population.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other study by Kucharska AM [35] examining the association between dietary acid load and cardio-metabolic risk factors among polish adults, only serum TG tended to increase across tertiels of NEAP only among men; while no significant difference among women or across PRAL tertiles were observed [35]. On the other hand, three studies reported lower TC or higher HDL concentrations in highest versus lowest categories of PRAL or NEAP [21, 34, 35]. Other studies reported no significant difference between lipids across NEAP or PRAL categories [11, 28, 31, 33, 35].…”
Section: Resultsmentioning
confidence: 96%
“…Imported fruits are costly and remain unaffordable to many people leading to a very low consumption of fruit 46. The benefit of fruits and vegetable consumption is primarily through increased intake of potassium 47 48. All vegetables may not contain high level of potassium and washing, and cooking may reduce potassium level 49.…”
Section: Discussionmentioning
confidence: 99%